2014
DOI: 10.21608/eajbsg.2014.16495
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papilloma Virus subtypes 52,56,58,59 and 66 among Yemeni Patients with Cervical Cancer

Abstract: Microbiology journal is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the research across the whole spectrum of the subject. These including bacteriology, virology, mycology and parasitology. In addition, the journal promotes research on the impact of living organisms on their environment with emphasis on subjects such a resource, depletion, pollution, biodiversity, ecosystem…..etc www.eajbs.eg.net Provided fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Then again, on testing the specimens for HPV subtype 18; 23/84 (27.4 %) were found positive and the remaining 61/84 (72.6 %) were revealed negative [ 19 ]. Another study from Yemen found that the prevalence of HPV subtypes 52,56,58,59, and 66, among cases was 0.6, 0, 4, 3.3 and 0 % respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then again, on testing the specimens for HPV subtype 18; 23/84 (27.4 %) were found positive and the remaining 61/84 (72.6 %) were revealed negative [ 19 ]. Another study from Yemen found that the prevalence of HPV subtypes 52,56,58,59, and 66, among cases was 0.6, 0, 4, 3.3 and 0 % respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bensumaidea and colleagues [95] examined cervical cancer tissue samples and reported 74% and 28% of the cases to be positive for HPV16 and HPV18, respectively. The same group further examined cervical cancer tissue samples in comparison with benign cervical lesion tissue (control) samples reporting the prevalence of HPVs -52, -56, -58, -59, and -66; in addition to HPVs -51 (0.6%), -58 (4%), and -59 (3.3%), the authors did not find HPVs -56 and -66 present among the cervical cancer cases, while only HPV 58 was identified in the controls (2%) [96]. On the other hand, a study conducted on cervical cancer samples from Yemeni women reported 24% of HPV positivity with prevalent subtypes, including HPV31 (7%), HPV33 (4%), HPV35 (4%), HPV39 (3%), and HPV45 (7%) [97].…”
Section: In Gcc Countries and Yemenmentioning
confidence: 86%
“…Notably, the methodology used for HPV DNA detection varied significantly amongst reviewed papers. Although the majority of studies used RT-PCR [74,[79][80][81][82][83][84]92,95,96,[99][100][101][102][103], others also used Hybird Capture 2 (HC2) [85], HPV linear array assay and direct sequencing [90], and hybridization reverse blot technique [98,105,106]. The highlighted differences in HPV detection technique used potentially affected the reported prevalence of HPV.…”
Section: In Other Countries Of the Mena Region And Turkeymentioning
confidence: 99%